2006
DOI: 10.1002/pmic.200401342
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of thePasteurella multocida outer membrane sub-proteome and its response to thein vivo environment of the natural host

Abstract: This study describes the identification of outer membrane proteins (OMPs) of the bacterial pathogen Pasteurella multocida and an analysis of how the expression of these proteins changes during infection of the natural host. We analysed the sarcosine-insoluble membrane fractions, which are highly enriched for OMPs, from bacteria grown under a range of conditions. Initially, the OMP-containing fractions were resolved by 2-DE and the proteins identified by MALDI-TOF MS. In addition, the OMP-containing fractions w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
76
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(77 citation statements)
references
References 49 publications
1
76
0
Order By: Relevance
“…One-quarter of the proteins that we identified are predicted to be membrane proteins, nearly one-third of the proteins are predicted to be cytoplasmic proteins, and the remainder have unknown localizations. As found in other gram-negative bacteria (6,16), including B. henselae (42), many of the proteins that fractionated with the TMP fraction are not membrane proteins. We performed a search of the B. quintana genome in the TIGR database for "membrane proteins" and identified 55 membrane-associated proteins.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…One-quarter of the proteins that we identified are predicted to be membrane proteins, nearly one-third of the proteins are predicted to be cytoplasmic proteins, and the remainder have unknown localizations. As found in other gram-negative bacteria (6,16), including B. henselae (42), many of the proteins that fractionated with the TMP fraction are not membrane proteins. We performed a search of the B. quintana genome in the TIGR database for "membrane proteins" and identified 55 membrane-associated proteins.…”
Section: Discussionmentioning
confidence: 69%
“…Four of the immunodominant antigens were OMP (VompA, VompB, HbpE, and Ppi). The remainder were predicted to be cytoplasmic proteins, and many of these cytoplasmic proteins have been identified previously in the outer membrane fractions of other gram-negative organisms, including other Bartonella species (6,16,42). Each of the 24 immunoreactive antigens commonly recognized by patients' sera was labeled in the immunoblot shown in 3.…”
Section: Resultsmentioning
confidence: 99%
“…However, while DNA microarray analyses comparing P. multocida gene expression during growth in iron -rich and iron -depleted medium identifi ed a large range of genes with altered expression; proteomic studies have revealed relatively few OMPs with altered expression in iron -depleted medium Boyce et al 2006 ).…”
Section: Iron -Regulated and Iron -Acquisition Proteinsmentioning
confidence: 99%
“…Spot trains of membraneassociated proteins were profiled in 2-DE gels after extraction/wash steps with Na 2 CO 3 at the pH of 11 in E. coli [27] and Pseudomonas aeruginosa [28]. Similar spot trains were also detected for proteins after extraction/wash steps with lauryl sarcosine at the pH of 7.5-7.8, in Helicobacter pylori [29] and Pasteurella multocida [30]. Two studies reported spot trains for membrane-associated proteins, following cell lysis at a pH of 7.5-8.0 without detergent or carbonate wash steps, in Borrelia burgdorferi [31] and E. coli [21].…”
Section: Resultsmentioning
confidence: 69%